Drugs, parents, and children the three-way connection - Rosenthal, Mitchell S.; Mothner, Ira (Boston Houghton Mifflin, 1972)
"Here is a book that refuses to coddle the illusions of either side of the generation gap about drugs and their dangers. It is a book written from intimate experience and clear knowledge. Above all, it is a book that can really help".--Cover.
Part one: Society's children are your kids -- The prevalence of druggism -- More vulnerable than others -- Starting out straight -- The adolescent storm -- Dealing with drugs -- The phoenix way -- Part two: The Adamses -- The browns -- The cowans -- A few final words.
Includes index.
Keywords: Youth -- Drug use; Parent and child